PENGARUH BAGI HASIL LITERASI KEUANGAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN MENGGUNAKAN PRODUK TABUNGAN KOPERASI BMT UGT SIDOGIRI KECAMATAN SUKUN KOTA MALANG - Zidni, Muhammad Tsabat; FITANTO, BAHTIAR (Islamic Economics and finance in Focus, 2022)
This study aims to determine whether there is a dependent relationship between the variables of financial literacy, trust and profit sharing on saving decisions. The number of respondents to the study was 100 traders from the Pasar Besar City of Malang, East Java, using a quantitative methodology. According to the results of research that has been done, there is a positive relationship between financial literacy, trust and profit sharing on saving decisions. . Of all the independent variables, those that have the greatest influence start from the trust variable of 0.630, the profit sharing variable of 0.366, and the financial literacy variable of 0.278. Thus this study suggests that the government and Islamic savings and loan cooperatives can increase socialization regarding the benefits of using savings products, as well as improve the quality and distribution of Islamic savings and loan cooperatives so as to increase public trust and interest in saving.